B2C Business Models for Museum and Cultural Travel Mixed Reality Solutions - Olli I. Heimo; Tuomas Mäkilä; Timo Korkalainen; Lauri Viinikkala; Teijo Lehtonen (Tampere, 2025)
In this paper B2C business models for cultural travel mixed reality solutions are analysed through both mobile application and video game business model frameworks. We argue that there are several business models that overlap both traditional application business in mobile ecosystems as well as video gaming and there are quite a few that are not (yet) feasible. This study presents a new improved model to comprehend and further analyse the MR business logic in museums and cultural travel business-to-customer business models.
Academic Mindtrek: Proceedings of the 20th International Academic Mindtrek Conference